CONSUMER ATTITUDE AND CONSUMER TRUST IN THE ONLINE SHOPPING MARKETPLACE - Mokoginta, Novia Amelia; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
In 2017 from the report of Asosiasi Penyelenggara Jasa Internet Indonesia, More than 50 percent or around 143 million people have been connected to the internet throughout that year. That way, almost the entire life of the Indonesian people is inseparable from the internet, internet is widely used by Indonesian People for various purposes including shopping, with many choices of online shopping marketplaces available today, online shopping marketplace is a way of buying and selling without face-to-face and separated in distance. This research is using qualitative research method that explores the theories from several journals, articles, books, and previous research. This research using qualitative method to examine the Consumer Attitude and Consumer Trust in the Online Shopping Marketplace. This research uses in-depth interview to collect data from ten informants. Informant were chosen by purposive sampling. The results of this study indicate that the attitudes held by consumers is a good attitude but consumers have not given full trust to the Online Shopping Marketplace.Keywords: Consumer Attitude, Consumer Trust.